Performance of admission control for multi-traffic in wireless communication network base on discrete time queue - LIU Ming-xing1; MA Zhan-you1 TIAN Nai-shuo2 (Tongxin xuebao)
An admission control scheme with priority for real-time traffic was designed, and a discrete time queue model Geo1 + Geo2/Geo1,Geo2/s,s（PP） was proposed to investigate the performance of the multi-traffic admission control scheme,which based on the wireless communication running mechanism and the variable QoS（quality of service） re- quirement of multi-traffic. The queue was analysised by using method of matrix-geometric solution, and the exact per- formance measure were obtained such as average queue length of both traffic, blocking probability of real-time traffic.